2020
DOI: 10.1177/1120672120960340
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of autologous plasma as adjuvant to pars plana vitrectomy in the treatment of high myopic full-thickness macular holes

Abstract: Background: To analyse the feasibility and efficacy of a novel autologous plasma rich in growth factor (PRGF) preparation as adjuvant to pars plana vitrectomy and internal limiting membrane peel in high myopic full-thickness macular hole (FTMH). Methods: Single-centre, single-surgeon retrospective chart review of consecutive patients with high myopic FTMH who underwent surgery with a minimum follow-up of 12 months. Patients were divided in group 1 (naïve) and group 2 (persistent). Quantitative and qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Following the standard method with ILM peeling and facedown positioning, repeat surgery of a persistent hole is mostly performed with revisional PPV with or without ILM peeling enlargement, which acts by removing the residual tangential tractions 9 , 19 . Other methods used in revisional surgery might be mentioned as induced retinal detachment through subretinal fluid injection, which releases the adhesions between the retracted retina and retinal pigment epithelium 20 , application of autologous blood products that modulate intraretinal gliosis through growth and neurotrophic factors 21 , and techniques that serve as plugging the hole and creating a scaffold for Müller cell migration and proliferation like free ILM flap, lens capsular flap, free retinal graft, or human amniotic membrane transplantation 19 , 22 , 23 , 24 , 25 . In general, among the multiple available surgical procedures, the surgeonʼs experience and preference determines the method selection.…”
Section: Discussionmentioning
confidence: 99%
“…Following the standard method with ILM peeling and facedown positioning, repeat surgery of a persistent hole is mostly performed with revisional PPV with or without ILM peeling enlargement, which acts by removing the residual tangential tractions 9 , 19 . Other methods used in revisional surgery might be mentioned as induced retinal detachment through subretinal fluid injection, which releases the adhesions between the retracted retina and retinal pigment epithelium 20 , application of autologous blood products that modulate intraretinal gliosis through growth and neurotrophic factors 21 , and techniques that serve as plugging the hole and creating a scaffold for Müller cell migration and proliferation like free ILM flap, lens capsular flap, free retinal graft, or human amniotic membrane transplantation 19 , 22 , 23 , 24 , 25 . In general, among the multiple available surgical procedures, the surgeonʼs experience and preference determines the method selection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reported closure rate of FTMH exceeds 95% [ 5 ], refractory cases persist. These cases have prompted attempts at additional interventions, such as extensive ILM peeling [ 6 ], inverted ILM flaps [ 7 ], autologous neurosensory retinal-free flap application [ 8 ], outpatient fluid-gas exchange (FGX) [ 9 ], and autologous platelet concentrates [ 10 ]. Notably, some study suggested that firm adhesion between photoreceptors and the retinal pigment epithelium hinders FTMH closure, leading to subretinal adhesion release using subretinal fluid applications [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of posterior staphyloma, the elongation of the axial length and epiretinal membrane formation render this surgery challenging and may elicit lower success rates. The inelasticity of the retinal blood vessels and internal limiting membrane (ILM) have also been considered to be an important factor in myopic MH surgery [2] . Several surgical methods have been defined to improve the outcomes of pars plana vitrectomy (PPV) and ILM peeling in the treatment of myopic, unclosed and large MHs, including free ILM patch transplantation and inverted ILM flap technique [3][4] .…”
Section: Introductionmentioning
confidence: 99%